2018
DOI: 10.4274/tdd.3478
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin is a Safety Therapy on Kidney: A Retrospective Study

Abstract: Objective: Isotretinoin is widely used in severe acne treatment. The drug leads to several adverse effects; skin and mucous membranes are frequently affected. It may also cause serious and fatal adverse effects like kidney damage. The aim of this study is to determine the safety of isotretinoin usage on kidney functions in patients with acne vulgaris. Methods: Eighty six patients with severe acne vulgaris and receiving 0.5 mg/kg/day of isotretinoin treatment were included in the study and evaluated retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, Parlak et al . in 2018 studied 86 patients in Turkey with severe acne vulgaris on isotretinoin, and measured serial serum creatinine levels and calculated the estimated glomerular filtration rate, and found that there was no significant difference in the baseline creatinine with the creatinine levels at 3 and 6 months, hence concluding that it is safe for the kidneys 13 . The current blood monitoring guidance for patients on isotretinoin by the British National Formulary (BNF) states that hepatic function and serum lipids should be measured before treatment, 1 month after starting and then every 3 months; it does not mention a need for monitoring renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Parlak et al . in 2018 studied 86 patients in Turkey with severe acne vulgaris on isotretinoin, and measured serial serum creatinine levels and calculated the estimated glomerular filtration rate, and found that there was no significant difference in the baseline creatinine with the creatinine levels at 3 and 6 months, hence concluding that it is safe for the kidneys 13 . The current blood monitoring guidance for patients on isotretinoin by the British National Formulary (BNF) states that hepatic function and serum lipids should be measured before treatment, 1 month after starting and then every 3 months; it does not mention a need for monitoring renal function.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,8 Contrary to this, there were no noteworthy differences in the baseline glomerular filtration rate between ISO and non-ISO users. 9 In dogs given ISO for 30 weeks at 20 or 60 mg/kg/day, testicular atrophy and lower spermatogenesis were eminent. 10 Despite its several pronounced side effects and without the regulated use, ISO was and is still being used extensively.…”
Section: Introductionmentioning
confidence: 98%